2018
DOI: 10.24106/kefdergi.378580
|View full text |Cite
|
Sign up to set email alerts
|

Sekizinci Sınıf Öğrencilerinin Matematiksel Muhakemeleri İle Uzamsal Yetenekleri Arasındaki İlişki

Abstract: The aim of this study is to determine the relationship between mathematical reasoning and spatial ability. The present study was carried out with 324 eighth-grade students. "Mathematical Reasoning Test" and "Spatial Ability Test" were used as data collection tools. In analyzing the data, Pearson's correlation coefficient between participants' scores of each test was computed. Results show that there is a significant positive correlation between mathematical reasoning and spatial ability. The relationship that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…One of the ways to make algebra concrete is to use multiple representation types in algebra teaching. Multiple representations facilitate algebra learning because they help to make algebra more concrete (Gürbüz & Şahin, 2015). This shows that multiple representations have an important place in algebra teaching and students should be able to use multiple representations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the ways to make algebra concrete is to use multiple representation types in algebra teaching. Multiple representations facilitate algebra learning because they help to make algebra more concrete (Gürbüz & Şahin, 2015). This shows that multiple representations have an important place in algebra teaching and students should be able to use multiple representations.…”
Section: Introductionmentioning
confidence: 98%
“…Cebir, sayı ve sembollerle belirli ilişkileri inceleyip, bu ilişkiler arasında genellemeler yapmayı sağlayan, içerisinde değişken, denklem, harfli ifade gibi birçok kavramı barındıran matematiğin önemli bir alanıdır (Akkaya & Durmuş, 2006;Vance 1998;Yağız, 2019). Matematiksel bir dil olan cebir, modern yaşam ve teknolojik gelişmeler için gereklidir (Dede & Argün, 2003;Gürbüz & Şahin, 2015).…”
Section: Introductionunclassified
“…There are a variety of studies in the literature regarding multiple representations (Gürbüz & Şahin, 2015;Panasuk & Beyranevand, 2010;Sert, 2007;Yıldırım & Albayrak, 2016). The number of these type of studies conducted within Turkey on this subject has also risen, especially in recent years (Ayyıldız & Aktaş, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a qualitative study, Gürbüz and Şahin (2015) investigated four eighth graders' transitioning skills between representations (verbal, table, equation, graph). In this study the representation transition that students found the most difficult tends to be from other representations to graphical representation, while the easiest transition is determined to be from other representations to table representation.…”
Section: Introductionmentioning
confidence: 99%
“…Uzamsal yetenek ile ilgili diğer bazı araştırmalarda ise uzamsal becerilerin matematik ve geometri (Cheng ve Mix, 2014;Kospentaris ve Spyrou, 2010;Lowrie, Logan ve Ramful, 2017), fen (Tracy, 1990), fizik (Delialioğlu ve Aşkar, 1999;Liner, 2012;Pallrand ve Seeber, 1984), kimya (Coleman ve Gotch, 1998;Pribyl ve Bodner, 1987), biyoloji (Russell-Gebbett, 1985, mühendislik (Peters, Chisholm ve Laeng, 1995) gibi alanlarla olan ilişkisi incelenmiştir. Dahası uzamsal yetenek ile ilgili bazı araştırmalarda da uzamsal beceriler ile uzamsal kaygı (Sarı, 2016), matematiksel muhakeme (Gürbüz, Erdem ve Gülburnu, 2018), mantıksal düşünme (Turgut, Yenilmez ve Balbağ, 2017), matematik kaygısı (Ferguson, Maloney, Fugelsang ve Risko, 2015) arasındaki ilişki incelenmiştir. Görüldüğü üzere uzamsal yetenek ile ilgili yapılan araştırmalar farklı amaçlar için yapılmış, araştırmalarda uzamsal yeteneğin farklı bileşenleri ele alınmış, farklı örneklemlerle çalışılmış, farklı araştırma yöntemleri, desenleri ve veri analiz yöntemleri kullanılmıştır.…”
Section: Introductionunclassified